Foreign body aspiration in adults - Invernizzi, Mariana; Romero, Lucía; Gruss, Ana; Berke, Andrés; Lapiedra, Ignacio (Cirugía del Uruguay, 2024)
This is a male patient, 28 years old, with a personal history of: asthma and problematic substance use. It is presented with an intake of a metal object approximately 10 cm long, with a larger diameter at one of its pointed ends (nail); occurred two hours before the consultation in the Emergency Department, followed by a brief episode of cough.